2011
DOI: 10.1590/s1984-70332011000200001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and genetic influences on sex expression in a backcrossed segregating papaya population

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
0
11
0
4
Order By: Relevance
“…Objetivando amenizar esta relação, a Universidade Estadual do Norte Fluminense Darcy Ribeiro vem, em parceria com a fazenda Caliman Agrícola S & A conduzindo ao longo dos últimos 15 anos, um programa de melhoramento genético do mamoeiro na expectativa de oferecer aos produtores cultivares e/ou híbridos de alto desempenho, adaptados e estáveis (Marin et al, 2006;Silva et al, 2008;Ramos et al, 2011).…”
Section: Introductionunclassified
“…Objetivando amenizar esta relação, a Universidade Estadual do Norte Fluminense Darcy Ribeiro vem, em parceria com a fazenda Caliman Agrícola S & A conduzindo ao longo dos últimos 15 anos, um programa de melhoramento genético do mamoeiro na expectativa de oferecer aos produtores cultivares e/ou híbridos de alto desempenho, adaptados e estáveis (Marin et al, 2006;Silva et al, 2008;Ramos et al, 2011).…”
Section: Introductionunclassified
“…Segregation of putative resistance genes is also the most likely explanation for the occurrence of infected plants in accessions classified as resistant. Ramos et al (2011) suggested that the Golden cultivar consists of a fixed non-genetic type and, consequently, is subject to high rates of segregation.…”
Section: Resultsmentioning
confidence: 99%
“…Floral anomalies reflect negatively on commercial fruit production, so the increased availability of varieties less sensitive to the influence of seasonality on sexual expression is of great importance for the cultivation of papaya and should reduce production fluctuations occurring throughout the year. As a consequence, the producer will have increased chances of success in crop exploitation (Ramos et al 2011).…”
Section: Introductionmentioning
confidence: 99%